The impact of multiculturalism on immigrant helping. Issue 3 (7th December 2012) - Mashuri, Ali; Burhan, Omar Khalifa; van, Esther
<x xml:space="preserve">Abstract</x> We examined how immigrants' acculturation style (multiculturalism versus assimilation) affects the host society's willingness to help immigrants. The results from this experiment supported our expectations in showing that multiculturalism triggered less immigrant helping than assimilation, but only among high national identifiers. In addition, immigrants pursuing multiculturalism were perceived as less warm than those pursuing assimilation, and perceived warmth mediated the interaction effect of identification and acculturation style on helping. Whereas help could improve immigrants' integration into the host society and reduce the degree to which the latter views immigrants as threatening, these results ironically demonstrate that immigrants who are viewed as most threatening receive the least amount of help.